PARADIGMA BARU BISNIS: POLA KARIER KERJA DAN IMPLIKASINYA PADA PERUSAHAAN DAN PEKERJA DEWASA INI - Yulius Koesworo (EKUITAS (Jurnal Ekonomi dan Keuangan), 2003)
The rapid development of information technology and globalization has changed business enviroment through its components: customers, competition and change (JC). Related to the 3 C, the changes can be categorized into three areas: (I) the area of customers, that is the moving of the power of market from producers to customers; (2) the area of competition, that is the moving of competition form domestic to global, (3) the area of change, that is moving of product life cyclefrom slow to rapid.As the consequence of the changes, like it or not, any business institution that intends to survive or keep existing has adjust its business paradigm to the current changes. In other words, the business institution has to develop its own paradigm or adopt the available business new paradigm.The adoption or application of the business new paradigm implies the changes of the nature job, the structure, the function of business organization and the domain of core business as well. The business new paradigm also change the pattern and meanings of working career and affects the business institution and individual worker.